2018
DOI: 10.14527/pegegog.2018.010
|View full text |Cite
|
Sign up to set email alerts
|

The effects of teaching applications with real life content on the levels of pre-service teachers' abilities to associate daily life with astronomy and electrical learning topics

Abstract: Students’ associating their knowledge with daily life demonstrates great significance in terms of understanding the importance of topics they learn in school as well as knowing where and how they are used in their daily life. In this context, teachers who will reflect these relationships in learning environments must have sufficient knowledge and experience. In this research, it was aimed to investigate the effects of teaching applications with real life content on the levels of pre-service teachers' abilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In addition, while some of the pre-service teachers did not think that some learning areas were related to daily life before the applications, they realised that they were aware of the existed relationships after the applications. In the study by Yalçın et al, (2018); the applications were arranged with the context-based learning applications in the astronomy and electric learning areas of the physics subjects with the preservice science teachers. As a result of the applications, it was found that the pre-service science teachers' association levels of the astronomy and electric learning areas with daily life increased and developed new contexts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, while some of the pre-service teachers did not think that some learning areas were related to daily life before the applications, they realised that they were aware of the existed relationships after the applications. In the study by Yalçın et al, (2018); the applications were arranged with the context-based learning applications in the astronomy and electric learning areas of the physics subjects with the preservice science teachers. As a result of the applications, it was found that the pre-service science teachers' association levels of the astronomy and electric learning areas with daily life increased and developed new contexts.…”
Section: Resultsmentioning
confidence: 99%
“…Because, in line with the theoric training given in the pre-service and in-service education, the pre-service teachers are insufficient in developing real-lifebased problems and do not have sufficient knowledge in the topic of context-based learning (Ayvacı, Ültay & Mert, 2013;Obay & Çelik, 2019). Application-based training should be given (Ültay, 2017; İnci & Çubukcu, 2018) to them or they should get an education directly with the context-based learning (Yalçın et al, 2018). This situation the context development, which is perceived as the most difficult part of life-based learning by teachers, that is, associating with life will be prevented (Gürsoy Köroğlu, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Pre-service science teachers' cognitive awareness levels are not adequate (Emrahoğlu & Öztürk, 2010) and they have problems with scientific creativeness (Demirhan, Önder, & Beşoluk, 2018). They cannot reflect scientific facts to daily life as expected (Balkan-Kıyıcı & Aydoğdu, 2011;Yalçın, Altun-Yalçın, Akar, & Sağırlı, 2018), which negatively affects pre-service teachers' levels of self-confidence towards their profession (Şenol, Akyol, & Can-Yaşar, 2018). Pre-service teachers lack experience in experimenting (Pekbay & Kaptan, 2014), that's why they develop negative attitudes towards laboratory (Ünal & Kılıç, 2016).…”
Section: Changes In General Competencies For Teaching Profession (Gctmentioning
confidence: 99%